Class and rural-urban migration - Johan Fredrik Rye; Arild Blekesaune (European Regional Science Association (ERSA), 2003)
The paper discusses rural to urban migration in modern Norway from a class perspective, focusing on to what extent actors in different social classes have distinct migration patterns. The analysis is based on Norwegian Census data from the period between 1960-90 (ten-yearly), and traces the social (e.g. education, occupation, and income) and geographic mobility of all Norwegians born in 1955. Data about their parents' social background are also employed. The number of cases is approximately 70,000. Theoretically the paper is based on a bourdieuian perspective. The point of departure is a hypothesis that young people from better-off rural families are the most likely ones to leave the countryside in favour of a more urban life, basically due to education motives. This is sought explained by employing Bourdieu's concepts of economic and cultural capital, and his claim that the objective class structures, which reflects unequal access to and composition of to these forms of capital, should be related to dif-ferences in the structures of subjective life-style (La Distinction, Bourdieu 1979). In this way migration decisions may be understood as results of class structured «lifestyle choices».
Keywords: 330